Decolonising justice for aboriginal youth with fetal alcohol spectrum disorders - Blagg, Harry; Tulich, Tamara; Williams, Robyn (Abingdon, Oxon ; New York, NY : Routledge, Taylor & Francis Group, 2021)
"This book reflects multidisciplinary and cross-jurisdictional analysis of issues surrounding Fetal Alcohol Spectrum Disorders (FASD) and the criminal justice system, and the impact on Aboriginal children, young people and their families. Early diagnosis and assessment of FASD may make a crucial difference to the life chances of Aboriginal youth and their families. Situated within a 'decolonising' approach, we explore the potential for increased diversion into Aboriginal community managed, on-country programs, enabled through innovation at the point of first contact with the police, and non-adversarial, needs focused courts. We argue for the radical recalibration of both theory and practice around diversion, intervention and the role of courts to significantly lower rates of incarceration - reducing the tendency for contributory outcomes inherent in imprisonment for people with cognitive impairments. We also argue that Aboriginal communities and families are best placed to construct the social and cultural scaffolding around vulnerable youth that could prevent damaging contact with the mainstream justice system. It brings together advanced thinking in criminology, Aboriginal justice issues, law, paediatrics, social work and Indigenous mental health and wellbeing, and is grounded in research undertaken in Australia, Canada and New Zealand. One of the key themes through the text is that, far from providing solutions to FASD, the mainstream criminal justice system increases the likelihood of adverse outcomes for children with FASD and their families. This book provides the first comprehensive and multidisciplinary account of FASD and its implications for the criminal justice system - from prevalence and diagnosis, to sentencing and culturally secure training for custodial officers"--
OCLC-licensed vendor bibliographic record.
Keywords: Fetal alcohol spectrum disorders; Children, Aboriginal Australian -- Criminal justice system; Children, Aboriginal Australian -- Social conditions; Alcohol -- Physiological effect; LAW / Criminal Law / Juvenile Offenders; SOCIAL SCIENCE / Criminology; SOCIAL SCIENCE / Social Work